Readjustment of the Paper [J. Kaur and S. S. Bhatia, Integrability and $L^1$-Convergence of Double Cosine Trigonometric Series, Anal. Theory Appl., 27(1) (2011), pp. 32-39] (Analysis in Theory and Applications, 2017)
In this paper, we show that new modified double cosine trigonometric sums introduced in [1] are inappropriate, the class of double sequences $J_d$ introduced there is unusable for such sums and consequently the results obtained in it are completely incorrect. We here introduce appropriate modified double cosine trigonometric sums making the class $J_d$ usable considering a particular double cosine trigonometric series.